THE EFFECT OF REACT MODEL TOWARD KNOWLEDGE COMPETENCE IN PHYSICS LEARNING - Rika Adhia Putri; Silvi Yulia Sari; Amali Putra; Renol Afrizon (Universitas Negeri Padang, 2023)
The physics outcomes of learning by students cannot be said to be good due to several factors including the lack of activity and Students' participation in the learning process and the lack of understanding of students of teacher for material presented. To overcome this, an appropriate model of learning is needed to overcome the above problems by using the REACT model. The research purposewas to find out whether there was a influence in significant on the influence of the REACT model on the achievement of knowledge competence in physics learning at Class XI SMAN 6 Padang. This research type includes Quasi Experiment Research. The research design used was the Posttess-Only Control Design. The research population were all class XI MIPA. The technique for sampling used was Purposive Sampling. Data on students' knowledge competency achievement were taken through the posttest using multiple choice questions. Based on the research data, The average value was discovered of the knowledge competency of the class for experimental was 81.94 and that of the class for control was 76.22. By carrying out a similarity test of two averages on knowledge competence at a significant level of 0.05, tcount > ttable is obtained. Thus the research results got conclussion that there is a influence in significant on the effect of the REACT model on the achievement of knowledge competence in learning physics at class XI SMAN 6 Padang.